Correlation of hemorrhage, axonal damage, and blood-tissue barrier disruption in brain and retina of Malawian children with fatal cerebral malaria - Greiner, Jesse; Dorovini-Zis, Katerina; Taylor, Terrie E.; Molyneux, Malcolm E.; Beare, Nicholas A. V.; Kamiza, Steve; White, Valerie A. (Frontiers in Cellular and Infection Microbiology, 2015)
Background: The retinal and brain histopathological findings in children who died from cerebral malaria (CM) have been recently described. Similar changes occur in both structures, but the findings have not been directly compared in the same patients. In this study we compared clinical retinal findings and retinal and cerebral histopathological changes in a series of patients in Blantyre, Malawi, who died of CM. Methods: The features systematically compared in the same patient were: 1) clinical, gross and microscopic retinal hemorrhages with microscopic cerebral hemorrhages, 2) retinal and cerebral hemorrhage-associated and -unassociated axonal damage, and fibrinogen leakage, and 3) differences in the above features between the pathological categories of CM without microvascular pathology (CM1) and CM with microvascular pathology (CM2) in retina and brain. Results: Forty-seven patients were included: 7 CM1, 28 CM2 and 12 controls. In the 35 malaria cases retinal and cerebral pathology correlated in all features except for non-hemorrhage associated fibrinogen leakage. Regarding CM1 and CM2 cases, the only differences were in the proportion of patients with hemorrhage-associated cerebral pathology, and this was expected, based on the definitions of CM1 and CM2. The retina did not show this difference. Non-hemorrhage associated pathology was similar for the two groups. Comment: As postulated, histopathological features of hemorrhages, axonal damage and non-hemorrhage associated fibrinogen leakage correlated in the retina and brain of individual patients, although the difference in hemorrhages between the CM1 and CM2 groups was not consistently observed in the retina. These results help to underpin the utility of ophthalmoscopic examination and fundus findings to help in diagnosis and assessment of cerebral malaria patients, but may not help in distinguishing between CM1 and CM2 patients during life.